Akanthomyces zaquensis (Cordycipitaceae, Hypocreales), a new species isolated from both the stroma and the sclerotium of Ophiocordyceps sinensis in Qinghai, China - Wang, Yong-Hui; Wang, Wen-Jing; Wang, Ke; Dong, Cai-Hong; Hao, Ji-Rong; Kirk, Paul M.; Yao, Yi-Jian (Phytotaxa, 2023)
An undescribed taxon of entomopathogenic fungi, Akanthomyces zaquensis, was introduced based on the collections from Duoxiao Village beside the Za Qu River in Qinghai Province, China. The taxon is characterized by its host and habitat of isolations from both the stroma and the sclerotium of Ophiocordyceps sinensis and by producing single and lanceolate or narrowly lageniform phialides directly from the aerial hypha. Phylogenetic analyses based on the combined ITS, SSU, LSU, tef1, rpb1 and rpb2 sequences supported the taxon as a new species of Akanthomyces.